2021
DOI: 10.3171/2020.7.jns201912
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial EEG and laser interstitial thermal therapy in MRI-negative insular and/or cingulate epilepsy: case series

Abstract: OBJECTIVE The goal of this study was to assess the success rate and complications of stereo-electroencephalogra-phy (sEEG) and laser interstitial thermal therapy (LITT) in the treatment of nonlesional refractory epilepsy in cingulate and insular cortex. METHODS The authors retrospectively analyzed the treatment response in 9 successive patients who underwent insular or cingulate LITT for nonlesional refractory epilepsy at their center between 2011 and 2019. Localization of seizures was based on inpatient vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Nearly all the depth electrode cases had some coverage of the insula or cingulate. Though insular and cingulate cortex epilepsies are rare, nonlesional insular and cingulate epilepsies are difficult to diagnose and may be misdiagnosed as temporal lobe epilepsy or frontal lobe epilepsy without utilization of depth electrodes in those regions 34 , 35 . Depth electrodes therefore provide a significant advantage in sampling the insula and cingulate, even if those regions may not be a part of the initial localization hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all the depth electrode cases had some coverage of the insula or cingulate. Though insular and cingulate cortex epilepsies are rare, nonlesional insular and cingulate epilepsies are difficult to diagnose and may be misdiagnosed as temporal lobe epilepsy or frontal lobe epilepsy without utilization of depth electrodes in those regions 34 , 35 . Depth electrodes therefore provide a significant advantage in sampling the insula and cingulate, even if those regions may not be a part of the initial localization hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Around one third of the patients experienced a temporary paresis. Gireesh et al, reported one intracerebral hematoma following LITT that required a decompressive hemicraniectomy, but subsequently had a good outcome ( 26 , 34 ). Bouthillier et al, recently published the results of 44 insulo-opercular cortectomies in 43 patients achieving a an Engel class 1 outcome in 77% (mean follow-up 6 years) with a 7% permanent postoperative deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, through a wider use of stereotactic electroencephalography (SEEG), insular epilepsy has been recognized as a separate diagnostic entity ( 23 ). Insular LITT was used for the treatment of epileptic lesions both in pediatric and adult cohorts ( 24 26 ). Laser interstitial thermal therapy compares favorably with other minimally invasive therapies for the treatment of drug resistant epilepsy (DRE), such as radiofrequency thermocoagulation (RFTC) with SEEG electrodes and gamma knife surgery (GKS) ( 23 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have focused on LITT for insular epilepsy. [36][37][38][39][40] LITT may be a better option, but volume-based RFTC is still a valuable alternative if LITT is not available. The laser probe with a diameter of 1.6 or 3.3 mm is used for LITT, and a cylindrical lesion is formed around the trajectory.…”
Section: Discussionmentioning
confidence: 99%